The Impact of Physical Activity on Lipid Profile and Dyslipidemia: What Type of Exercise Is Most Effective in Preventing Cardiovascular Diseases? - Kowalczyk, Olga; Kozłowski, Sebastian; Bulicz, Anna; Zdunek, Marta; Stodulski, Maciej; Kasprzycka, Izabela; Fiks, Justyna; Kukla, Monika; Dziarnowska, Joanna; Kmiecik, Izabela (Quality in Sport, 2026)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide. Dyslipidemia significantly contributes to atherosclerosis, endothelial dysfunction, and chronic vascular inflammation, increasing the risk of ischemic cerebral and cardiac events. Regular physical activity is a key component of cardiovascular prevention due to its beneficial effects on lipid metabolism and systemic inflammation. The study aimed to evaluate the impact of physical activity on lipid profile parameters and cardiovascular risk, with particular emphasis on the effects of aerobic, resistance, high-intensity interval training (HIIT), and combined exercise models on LDL-C, HDL-C, and triglyceride levels. A narrative literature review was performed using PubMed and Google Scholar databases. The search included keywords such as “dyslipidemia,” “lipid profile,” “physical activity,” and “cardiovascular risk.” Original studies, randomized controlled trials, systematic reviews, meta-analyses, and current clinical guidelines on cardiovascular prevention were analyzed. Regular physical activity improves lipid profile by lowering LDL-C and triglyceride levels while increasing HDL-C concentration. Aerobic exercise is the most extensively studied modality in cardiovascular prevention and demonstrates significant cardioprotective effects. Resistance training improves insulin sensitivity and body composition, indirectly supporting lipid metabolism. HIIT induces rapid metabolic adaptations and may be an effective alternative for selected patients. Combined training integrates the benefits of aerobic and resistance exercise, providing comprehensive cardiovascular and metabolic effects. Regular physical activity, regardless of exercise type, plays a fundamental role in improving lipid profile and reducing cardiovascular risk. The greatest benefits are associated with combined training programs and regular moderate-intensity aerobic exercise.